Prospective Cohort Study of Central Adiposity and Risk of Death in Middle Aged and Elderly Chinese. - Shaneda Warren Andersen; Xiao-Ou Shu; Yu-Tang Gao; Xianglan Zhang; Hui Cai; Gong Yang; Hong-Lan Li; Yong-Bing Xiang; Wei Zheng (PLoS ONE, 2015)
Asians have high prevalence of central obesity despite the low prevalence of general obesity. We evaluated associations between the central obesity measure, waist-hip ratio (WHR) with total and cause-specific mortality in middle-aged and elderly Chinese participants. Data arise from two prospective population-based cohort studies: the Shanghai Men's Health Study involves 53,425 men (participation rate = 74.0%), age 40-74 at baseline, and the Shanghai Women's Health Study involves 63,017 women (participation rate = 92.7%), age 40-70 at baseline. Information on lifestyle factors and anthropometric measurements were taken at baseline interview. Vital status and causes of death were obtained via surveys and annual linkages to relevant Shanghai registries through December 31, 2011. After median follow-up time of 7.5 years for the Shanghai Men's Health Study and 13.2 years for the Shanghai Women's Health Study, there were 2,058 and 3,167 deaths, respectively. In models adjusted for BMI and other potential confounders, WHR was associated with all-cause mortality; hazard ratios (HRs) (95% confidence intervals) across the first to fifth quintile increased from 1 (Reference), 1.10 (0.95,1.27), 1.21 (1.04,1.41), 1.11 (0.96,1.30), to 1.42 (1.22,1.65) in men and from 1 (Reference), 1.10 (0.96,1.27), 1.11 (0.97,1.27), 1.20 (1.05,1.37), to 1.48 (1.30,1.69) in women. WHR had a stronger association with cardiovascular disease, with multivariate-adjusted HRs of 1.5 to 1.7 observed for the highest versus lowest quintile of WHR. Dose-response associations were also seen for cancer and other-cause deaths. Stratified analyses suggested a stronger association with mortality among normal weight (BMI <25) than over-weight (BMI ≥25) individuals. Positive associations with mortality were observed in subgroups defined by follow-up duration, comorbidity, age, smoking, and physical activity. Greater central adiposity is associated with increased mortality in Chinese adults, even among individuals with low BMI. Physicians and the public should be aware of central adiposity's independent effects on health.